RTS noise characterization of GaN on silicon based HEMT - Xiong, Chenxi. (2012)
This project aims to investigate the RTS noise for GaN on Silicon based HEMTs for various bias voltages, and characterize the RTS noise by employing a statistical approach. By measuring the RTS noise for GaN on Silicon based HEMT under different bias voltage, we would be able to recognize the trends reflected in the statistics and explained them reasonably. In cases where the charges have a significant impact on transistor performance, the output signal can be substantial. Thus, it would be meaningful to investigate the nature of RTS for transistors in both time and frequency domain.